Impacto del uso de la ciencia dactiloscópica, en la investigación criminal (2014)
This case study relating to theft and murder succinctly establishes the characteristics and variables that may occur in the commission of these offenses in Colombia as the Colombian penal system aims to intervene in specific parts such as the factor of violence that occurs in our country, the mechanism used to carry the offense, the actor or participant in this event and the importance of fingerprint techniques, were to lead to the clarification of the facts of the investigation and the punishment to be imposed according to offender and committed criminal offense